What Really Matters in Old Age? A Study of Older Adults’ Perspectives on Challenging Old Age Representations - Sofia von Humboldt; Gail Low; Isabel Leal (Social Sciences)
Aim: Older age is not a homogenous or stereotypical experience. Age-stereotypical representations can often be disconnected from older people’s own experiences. Challenging the status quo is relevant for aging well. The aim of this study is to analyze older adults’ perspectives on stereotypical versus their own age representations. Method: This qualitative study included a sample of 433 older adults who were 65 to 74, 75 to 84, and 85+ years of age. Content analysis was carried out. Results: Findings from this study indicated that the great majority of the participants (88%) did not identify with stereotypical age representations. This was so among participants in the 65–74 age group in relation to Showing a sense of agency (81.1%); Feeling spiritual (73.4%); Having meaningful goals (72.2%); Holding a significant social network (70.9%); Staying tuned to the world (67.1%); and feeling physically attractive (59.8%). Participants who were 75–84 years of age clarified what physical health (81.0%) and surviving chronic illnesses (78.9%), autonomy (75.5%), being socially active (74.9%), and staying mentally active (70.1%) represent at that age. The +85 years age group drew attention to No pain or physical limitations (95.6%), Physical health (93.1%), Cognitive autonomy (87.1%), Staying tuned to society and the world (76.3%); and Mobility (72.2%). Conclusions: Participants’ favoring their own over stereotypical thinking about people their age represents inner resourcefulness and a penchant for aging well. Collaborative partnerships for sharing such wisdom around could enrich policy programs and interventions that favor inclusivity and fight ageism, fostering a more accurate perspective of what it means to be a certain ‘age’ versus simply being ‘old’.